Highly Efficient Synthesis of Heterocyclic and Alicyclic β2‐Amino Acid Derivatives by Catalytic Asymmetric Hydrogenation. Issue 9 (17th June 2013) - Li, Lanning; Chen, Bin; Ke, Yuanyuan; Li, Qing; Zhuang, Yue; Duan, Kun; Huang, Yichun; Pang, Jiyan; Qiu, Liqin
Abstract A valuable class of new heterocyclic and alicyclic prochiral α‐aminomethylacrylates has been conveniently synthesized through a three‐step transformation involving a Baylis–Hillman reaction, O‐acetylation, and a subsequent allylic amination. The corresponding novel β2‐amino acid derivatives were prepared with excellent enantioselectivities and high yields by catalytic asymmetric hydrogenation using the catalyst rhodium(Et‐Duphos) (Et‐Duphos=2′, 5′, 2′′, 5′′‐tetraethyl‐1, 2‐bis(phospholanyl)benzene)) under mild reaction conditions (up to 99 % ee and S/C=1000). The influence of the substrate on the enantioselectivity and reactivity is investigated, and the most suitable substrate configuration for the highly efficient enantioselective hydrogenation of β‐substituted α‐aminomethylacrylates under the Rh–Duphos system is reported. The current protocol provides a very practical, facile, and scalable method for the preparation of heterocyclic and alicyclic β2‐amino acids and their derivatives.